Mechanical and antimicrobial performance analysis of a shark skin bio-mimicked fabric swatch via 3D printing - Purandare, Saloni Prasanna, author; Li, Yan Vivian, advisor; Yan, Ruoh-Nan, committee member; Prawel, David, committee member (Colorado State University. Libraries, 2020)
Biomimicry is a long-practiced concept concerned with development of products with nature as the source of inspiration. Bio mimicked textiles is a branch of textiles wherein textile products are developed to replicate desirable elements of nature such as lotus-leaf inspired water repellent fabric, high-strength spider silk inspired by the spider web and shark skin biomimicry. The scaled texture on shark skin, known as riblet effect, exhibits drag reduction and antimicrobial properties. Accurate biomimicry of shark skin is an on-going continual process This study is concerned with 3D printing bio mimicked fabric swatches by replication of riblet effect followed by characterization of the developed fabric swatches. The swatches were printed using Autodesk Ember photopolymer 3D printer, allowing printing of minutely detailed denticles in the base. The materials used were polycarbonate/acrylonitrile butadiene styrene (PC/ABS) and polyurethane (PU) material. PU allowed creation of rigid tough denticles embedded in flexible and soft base, indicating as a better raw material to 3D print bio-mimicked swatches for functional clothing. The PU swatches were studied further in morphological, mechanical, and antimicrobial analysis. The morphological analysis resulted into optical images exhibiting the developed texture resembling characteristic riblet effect of shark skin. Mechanical analysis in terms of tensile stress testing exhibited stronger and tougher fabric samples with thick (1.05mm) base in comparison with those having thin (0.75mm) base. Also, the mechanical analysis indicated good elastomeric properties for the fabric swatches suggesting potential in functional clothing. Lastly, the antimicrobial test conducted exhibited reduced antimicrobial growth for samples with riblet texture against untextured samples, copper foil as well as aluminum foil thus exhibiting potential use of the textured fabric swatches as non-toxic antimicrobial material. Shark skin biomimicry through riblet effect replication has been studied majorly for hydrodynamic properties while shark skin inspired material intended for antimicrobial properties such as by Sharklet® technology is not concerned with riblet effect replication. Thus, to our best knowledge study focusing on mechanical and antimicrobial analysis of shark skin biomimicry through replication of riblet effect is missing. This study will help determine potential of shark skin biomimicry by replication of riblet effect in functional clothing, through mechanical and antimicrobial analysis.
Keywords: antimicrobial property; shark skin biomimicry; tensile stress test; riblet effect; 3D printing